The experimental study of pathological changes of visceral leishmaniasis in dog in Basrah province - Dawood Salman Mahdi (University of Thi-Qar Journal of Science, 2019)
The aim of this study was to evaluate the histopathological effect of leishmaniasis on liver and spleen ofdog. Five dogs were inoculated with leishmania in laboratory to study variable histopathological change inrelation to serological analysis. Section of liver and spleen were cut and stained with Leishman andhaematoxylin and eosin stain for microscopical examination. Liver was show a pseudolobule, fewinflammatory cells infiltration mostly lymphocytes and plasma cells and liver parenchyma is absent with afew necrotic hepatocytes with areas of fibrosis. Spleen was greatly enlarged, section of it shown few sinusoidshave large numbers follicular structures,eosinophilic hyalinized wall of blood vessels ,multiple areas ofnecrosis and destroying the normal architecture white pulp, red pulp is largely occupied by collection ofmacrophages (histiocytes). When compared with natural dog that have negative serological test.